2022
DOI: 10.1590/s1980-657420220004822
|View full text |Cite
|
Sign up to set email alerts
|

Mental fatigue and ball sports: a narrative review focused on physical, technical, and tactical performance

Abstract: This narrative review aimed to explore the effect of mental fatigue on physical, technical, and tactical performance in ball sports. Methods: Three Databases, PUBMED, SCOPUS, and SCIELO, were used to search for a scientific publication. The criterions adopted were: a) published in a peer-reviewed journal; b) adopted at least one manipulation check related to mental fatigue; c) mental fatigue induced by a cognitive task before the outcome task, and d) study participants were ball sports athletes. Result: The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Since another recent review indicated that the impairment of performance during SSG could not be conclusive (Costa et al, 2022 ), there are several questions raised, for example, could the non-significant effect of MF on physical performance measured as intermittent endurance be from the less demand in the possession format of SSG in the study of Badin et al ( 2016 )? Are the number of athletes on each side of SSG in the study of Coutinho et al ( 2017 ) too big to induce the adverse effect?…”
Section: Discussionmentioning
confidence: 99%
“…Since another recent review indicated that the impairment of performance during SSG could not be conclusive (Costa et al, 2022 ), there are several questions raised, for example, could the non-significant effect of MF on physical performance measured as intermittent endurance be from the less demand in the possession format of SSG in the study of Badin et al ( 2016 )? Are the number of athletes on each side of SSG in the study of Coutinho et al ( 2017 ) too big to induce the adverse effect?…”
Section: Discussionmentioning
confidence: 99%